Location planning of flexible direct-current interconnection control device for distribution network based on optimal power flow - Qiu, Zhiyong; Mo, Yuanbin (Expert systems with applications, 2025)
•We explored the optimal deployment locations for control devices.•We presented an OPF model with control equipment and design a hybrid optimization algorithm.•We used SDR to relax the non-convex model into a convex one, and then solved the relaxed model using SDP.•We used SGA to explore the deployment information. The flexible direct-current interconnection control equipment is a flexible and effective means to improve flow distribution and reduce power loss. This paper addresses the location and operational strategy problem of soft open points and rotating flow controllers based on optimal power flow, a hybrid optimization algorithm is designed. Firstly, the operational models of soft open points and rotary power flow controllers are analyzed, a general optimal power flow model considering both soft open points and rotary power flow controllers is proposed. It is modeled using semidefinite programming and simultaneously considers safety and operational constraints. Secondly, a hybrid optimization algorithm is designed: the inner layer relies on a semidefinite programming algorithm to solve the optimal power flow problem with control equipment, while the outer layer employs a binary snow geese algorithm to explore the optimal installation quantity, capacity, and location information of the control equipment. Finally, to verify the feasibility of the proposed model and algorithm, simulations are conducted on two IEEE 33 Bus benchmark interconnected distribution system and two IEEE 141 Bus benchmark interconnected distribution system, and simulation was carried out on a distribution network in the real world. The simulation results indicate that the result obtained from the proposed hybrid algorithm can improve flow distribution, significantly reduce power loss, lower the risk of voltage violations, and reduce overall operational costs in most scenarios.